The autoantibody frequency in patients with drug allergy - Papatya Bayrak Değirmenci; Zeynep Altın (SERNEV, 2022)
Introduction: This study is aimed to analyze the autoantibody frequency in patients with drug allergy. Descriptive, observational research on drug allergy will contribute to the creation of new hypotheses about the pathophysiology of autoimmunity.Methods: The data of patients who were registered in the Training and Research Hospital database until the end of December 31, 2018 and diagnosed with drug allergy were retrospectively evaluated. Overall, 617 adult patients who had been diagnosed as "allergy status to drugs," according to ICD 10, and had had at least one autoantibody result were included in the study.Results: The frequency of having at least one autoantibody varied between 0% and 92.1%. The most commonly detected autoantibody was rheumatoid factor (RF) (n = 241; 92.1%). The second most common one was anti-tissue transglutaminase IgA antibody (Anti-tTG-IgA) (n=22; 68.2%). The frequencies of anti-thyroglobulin (Anti-TG), anti-thyroid peroxidase (anti-TPO), and anti-double stranded DNA (Anti-dsDNA) were 65.2% (n = 155), 59.7% (n = 159), and 43.6% (n= 55), respectively.Conclusions: Many drugs can trigger the development of autoantibodies with no progression to autoimmune disease. Autoantibodies should be suspected in patients with allergies to medications. Observational research on drug allergy will contribute to the creation of new hypotheses about the pathophysiology of autoimmunity. Numerous studies in this area can enable us to discuss the widespread use of risky drugs in a more objective way. We think that our study will shed light on the relationship between drug reaction and autoimmune diseases.Keywords: Autoantibodies, autoimmunity, drug allergy, drug hypersensitivity